The influence of supply chain responsiveness, collaboration and information sharing on the performance of small to medium enterprises in a district municipality - Mba, Eucharia Akuoma (Vaal University of Technology, 2020)
Supply chain management is becoming more complex for small- and medium enterprises (SMEs) and the need to improve performance seems to be significantly necessary. For SMEs to be efficient and effective towards minimising disruptions within supply chains, ensuring availability of resources and improving just-in-time delivery, information sharing coupled with supply chain collaboration and responsiveness are essential strategies for enhancing business performance. Therefore, this study regards supply chain collaboration, responsiveness and information sharing as major factors influencing not only SMEs performance. In this study, a quantitative research methodology was applied. Relational governance theory (RGT) provided structure to a clear understanding of information sharing among SMEs and customers. The theory highlighted that SMEs aiming to improve their performance, should adopt the style of collaborating with the right suppliers and continuously communicate with the members of the supply chains. This structure guided the researcher towards planning, implementing and evaluating the research findings. An overview of the research methodology and the techniques used in the study are presented, including the Statistical Packages for Social Sciences (SPSS version 25.0 Windows) used to analyse and determine the reliability and validity of the research instrument. Results acquired show a strong relationship between the four constructs. Confirmatory factor analysis (CFA) and structural equation modelling (SEM) results support the empirical findings, suggesting that the model fit the study. The reliability and validity of the constructs (composite reliability) and the average variance extracted sought the empirical findings that correlate the need for SMEs to employ information sharing, supply chain responsiveness and supply chain collaboration as a determinant influence on SMEs performance. The Cronbach alpha values ranges from 0.823 to 0896 and AVE results ranges from 0.500 to 0.625 respectively which indicate acceptable reliability and validity for this study. It is recommended that as focused responsiveness is critical, all efforts made by SMEs must be expanded in order to determine what constitutes desired responsiveness for individual members in the supply chain. Differentiated and highly responsive programmes for key members of the supply chain should be impartial with supply chain members oriented but less tailored approaches for lesser involved members. Enough and important information must be obtained in order to identify the member’s requirements.
M. Tech. (Department of Logistics Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Small and Medium Enterprises; Supply chain management; Just-in-time delivery; Improve information sharing; Dissertations, Academic -- South Africa.; Business logistics.; Small business.